Menelaah Makna Tersembunyi Dalam Lirik Lagu “Istirahat” Nosstress - Syakhila Octaviani; Nazwa Nurfauziah (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
The song "Istirahat" by Nosstress is a song that tells about environmental concern, about the earth that seems to be getting damaged and worse due to the actions of its inhabitants, namely humans themselves. Nosstress is known as a music group that often raises environmental, socio-political, and humanitarian issues, which are conveyed simply through their works. This songwriter tries to express his feelings by inspiring his listeners to rest just a little while, giving time to the earth, we can see in the lyrics "Hi my human friends, just rest a little, for him and the human earth". The aims of this study are (1) to find out the meaning contained in the lyrics of the song "Istirahat" by Nosstress, (2) to explain what figurative language is contained in the lyrics of the song "Istirahat" by Nosstress. This research is based on curiosity about the meaning of the song lyrics which are quite poetic and the figurative language used by the author in the song. The method used in this research is qualitative method. The results of this study are understanding the structure, meaning, and figure of speech in the lyrics of the song "Istirahat" by Nosstress.